Self-incompatibility alleles in Esatern European and Asian almond (Prunus dulcis) genotypes: a preliminary study - B. Szikriszt; S. Ercisli; A. Hegedűs; J. Halász (International Journal of Horticultural Science, 2012)
Almond [Prunus dulcis (Mill.) D. A. Webb.] as one of the oldest domesticated plants is thought to have originated in central Asia. Gametophytic self-incompatibility of almond is controlled by the highly polymorphic S-locus. The S-locus encodes for an S-ribonuclease (S-RNase) protein in the pistils, which degrades RNA in self-pollen tubes and hence stops their growing. This study was carried out to detect S-RNase allelic variants in Hungarian and Eastern European almond cultivars and Turkish wild growing seedlings, and characterize their S-allele pool. Five new alleles were identifi ed, S31H, S36-S39 in Eastern European local cultivars. The village Bademli and Akdamar island are two distinct places of almond natural occurrence in Turkey. Trees growing wild around Bademli city showed greater genetic diversity than those originated on Akdamar island. Many of the previously described 45 S-RNase alleles have been also detected in these regions. Homology searches revealed that Turkish almonds carried some P. webbii alleles indicating hybridization between the two cultivars and massive introgression events. Our results supply long-awaited information on almond S-allele diversity from regions between the main cultivation centres and the centre of origin of this species; and are discussed from the aspect of methodological developments and evolution of the cultivated almond.